Feeding Ecology of Roe Deer, Capreolus capreolus L., during summer in southeastern Norway - Vidar Selås; Gunnar Bjar; Ola Betten; Lars Olav Tjeldflaat; Olav Hjeljord (Fauna Norvegica)
Ten radiocollared Roe deer were followed over three summers, resulting in 2316 map locations. The animals utilized a mixture of forest and agricultural land. Cover and forage availability were the main determinants of habitat selection. Forest plantations on rich sites were the most preferred habitat. Open habitats like meadows were used mostly at night. Grain-fields were avoided. The animals fed on a variety of forbs and browse species, particularly wood anemone (Anemone nemorosa L.) in early spring, and meadosweet (Filipendula ulmaria L.) throughout the summer. Browsing increased from early to late summer. This coincided with a change in the feeding-resting rhythm, indicating a decrease in overall forage quality. Carrying capacity of the study area is discussed in relation to quality of summer habitat.